(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
In this article, students’ daily activities, students’ routines and the culture of using mobile devices, prevention of harmful habits in students, ways to get rid of stress, and meaningful organization of students’ free time are described in this article.